Nasal endoscopy: an excellent tool for the novice - Suraneni, Visweswara Rao; Kudamala, Suneel; Begum, Karishma (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Nasal endoscopy has revolutionized the ease of diagnosing nasal pathologies over the recent years. It offers the advantage of detailed examination of the intra-nasal architecture and precise identification of the pathology. It is cost effective and a useful adjunct for performing minor procedures in the office setting. Thus, nasal endoscopy has evolved as a tool with multiple roles of diagnosing the disease, planning of treatment and post treatment examination. Methods: This is a prospective study conducted at a tertiary care hospital during a period of 2 years on 100 patients to evaluate the role of nasal endoscopy in diagnosing the disease and planning the management. 60 cases were managed conservatively depending on the initial finding on nasal endoscopy while the other 40 cases underwent surgery. Pre-treatment symptoms and post treatment outcomes were observed objectively on nasal endoscopy. Results: Majority of the patients (60%) were managed conservatively and were labeled as cured after enough evidence was obtained both subjectively from the patient and objectively as seen on endoscopy. The remainder of patients (40%) underwent surgery and follow up endoscopy was done in all of them. Conclusions: Diagnostic nasal endoscopy is of immense help to the novice surgeon in understanding and managing various nasal pathologies. Through this study, it can be concluded that most of the nasal symptoms can be managed conservatively and surgery advised for absolute indication, with the help of nasal endoscopy.